ANALYSIS OF THE IMPACT OF FINANCIAL LITERACY, PERCEIVED EASE OF USE AND PERCEIVED USEFULNESS ON THE EFFECTIVENESS OF PERSONAL FINANCIAL MANAGEMENT WITH TRUST AS A MEDIATING VARIABLE - Sulhan, Muhammad (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2025)
The current digital era has brought various innovations that have transformed the way personal finances are managed, especially through fintech platforms. The effectiveness of personal finance management plays a vital role in achieving financial well-being. This study aims to examine the relationship between financial literacy, perceived ease of use, perceived benefits, and trust in the effectiveness of personal finance management of MSMEs through the use of fintech e-wallets. This study applies a quantitative approach with an explanatory research type. The population in this study is MSMEs in the Malang city area by taking a sample of 150 respondents of MSMEs in Malang city who use fintech in the form of e-wallets in their business transactions. Data analysis in this study uses the Structural Equation Modeling approach with the Partial Least Square (SEM-PLS) method operated through SmartPLS 4 software. The results of this study indicate; First, Financial literacy has a significant positive effect on the effectiveness of personal finance management; Second, Ease of use has a significant positive effect on the effectiveness of personal finance management; Third, Perceived benefits have a significant positive effect on the effectiveness of personal finance management; Fourth, Trust is able to mediate the influence between financial literacy and the effectiveness of personal finance management; Fifth, Trust is able to mediate the influence between ease of use on the effectiveness of personal financial management; Sixth, Trust is able to mediate the influence between perceived benefits on the effectiveness of personal financial management.